Enhancing the polymer electrolyte – Li metal interface on highvoltage solid-state batteries with Li-based additives inspired by the surface chemistry of Li₇La₃Zr₂O₁₂ - Oruea, Ander (2022)
High-voltage Li metal solid-state batteries are in the spotlight of high energy and power density devices for the next generation of batteries. However, the lack of robust solid-electrolyte interfaces (SEI) and the propagation of Li dendrites still need to be addressed for practical application with extended cyclability. In the present work, high-voltage Li metal cells with LiNi0.6Mn0.2Co0.2O2 active material were assembled with a polyethylene(oxide) based electrolyte mixed with bis(fluorosulfonyl)imide (LiFSI) salt. The addition of Li7La3Zr2012 garnet to form a composite electrolyte demonstrated the beneficial effect for cell cycling stability. Inspired by the improved interface of ceramic Li7La3Zr2012 garnet and Li metal, as well as by previous knowledge on favorable SEI forming species, various additive candidates were selected to optimize its electrolyte composition. Among them, lithium hydroxide (LiOH) is a key favorable specie that shows a relevant improvement on the cyclability of the cells. X-ray photoelectron spectroscopy showed that the SEI layer is composed mainly by chemical species arising from the reduction of the Li salt, being the lithium fluoride (LiF) the main product. In addition, solid-state nuclear magnetic resonance proved that LiOH induces the cleavage of the labile S-F bond, increasing the concentration of LiF. Herein, we highlight that SEI-forming additives need to be considered for the interfacial engineering design of stable SEI to expand the performance boundary of SSBs.